CASTLEMAN DISEASE VARIANT OF POEMS SYNDROME: A CASE REPORT AND LITERATURE REVIEW - LI Yuxin, XU Xiang, ZHANG Xiaolin, XING Baodi, ZHAO Wenjuan, HAO Dapeng, LIU Bin, CHEN Yunqing, DONG Bingzi, WANG Zhongchao, SUN Xiaofang, ZHAO Yuhang (精准医学杂志, 2023)
Objective To improve the awareness of POEMS syndrome among clinicians, and to increase the experience in the clinical diagnosis and treatment of atypical POEMS syndrome. Methods A retrospective analysis was performed for the cli-nical data of a patient with Castleman disease variant of POEMS syndrome who were hospitalized in Department of Endocrinology in our hospital in September 2020, and a literature review was performed. Results The patient had the initial manifestation of endocrine abnormality (hypogonadism), followed by other manifestations such as skin damage, neurogenic damage, multiple serous effusion, and multiple lymph node enlargement, which were consistent with the diagnostic criteria for POEMS syndrome, but hematological examination showed no evidence of clonal plasma cells. After multidisciplinary consultation and lymph node biopsy, pathological examination suggested Castleman disease, with an increase in the level of vascular endothelial growth factor (VEGF) in plasma, and finally the patient was diagnosed with Castleman disease variant of POEMS syndrome. Conclusion Clinicians need to have pluralistic thinking in the diagnosis and treatment of POEMS syndrome, and when POEMS syndrome is highly suspected in clinical practice without fully meeting necessary diagnostic criteria, they should actively look for relevant evidence and emphasize the value of lesion biopsy and plasma VEGF level in the diagnosis of this disease, so as to reduce missed diagnosis and misdiagnosis.